1991
DOI: 10.1677/joe.0.1300129
|View full text |Cite
|
Sign up to set email alerts
|

Hormonal regulation of insulin-like growth factor (IGF)-binding proteins secreted by isolated sheep thyroid epithelial cells: relationship with iodine organification

Abstract: Isolated sheep thyroid follicles release specific insulin-like growth factor-binding proteins (IGFBPs). Since IGFBPs can modulate IGF bioactivity, at least in vitro, their presence in thyroid tissue may influence synergistic interactions between TSH and endogenous IGF-I or -II which are known to control both thyroid growth and function. We have examined the hormonal control of IGFBP release in relation to iodine organification. Sheep thyroid follicles were isolated by incubation with collagenase and differenti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
13
0

Year Published

1994
1994
2000
2000

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(17 citation statements)
references
References 38 publications
4
13
0
Order By: Relevance
“…This observation, coupled with the finding that IGFBP-2 production by fetal lung epithelial cell cultures declines with increasing cell density (39), suggests that the decreased expression of IGFBP-2 on E21 may reflect the increase in epithelial cell density during this developmental period or changes in epithelial cell-cell interaction as differentiation proceeds. For example, in porcine follicular thyroid cells, the relative abundance of IGFBP-2 determines whether these cells respond to IGF-II by proliferating or by increasing differentiated cell function (40). Thus, these observations are consistent with IGFBP-2 facilitating the accumulation of IGF-I and IGF-II on the epithelial cell surface, possibly modulating the proliferative and/or differentiative effects of the IGFs on airway epithelium.…”
Section: Discussionsupporting
confidence: 58%
“…This observation, coupled with the finding that IGFBP-2 production by fetal lung epithelial cell cultures declines with increasing cell density (39), suggests that the decreased expression of IGFBP-2 on E21 may reflect the increase in epithelial cell density during this developmental period or changes in epithelial cell-cell interaction as differentiation proceeds. For example, in porcine follicular thyroid cells, the relative abundance of IGFBP-2 determines whether these cells respond to IGF-II by proliferating or by increasing differentiated cell function (40). Thus, these observations are consistent with IGFBP-2 facilitating the accumulation of IGF-I and IGF-II on the epithelial cell surface, possibly modulating the proliferative and/or differentiative effects of the IGFs on airway epithelium.…”
Section: Discussionsupporting
confidence: 58%
“…However, in several other in vitro studies [37,38,39,40] IGFBP-2 expression was found to correlate positively with cell proliferation. It was thus concluded that IGFBP-2 represents an inducer of cell growth rather than an inhibitor.…”
Section: Investigation Of Igfbp-2 Functions In Cell Culture Studiesmentioning
confidence: 82%
“…Secretion of several types of IGF binding proteins by thyrocytes has been demonstrated (16)(17)(18). Studies on mesenchymal as well as epithelial cells shows that the expression of general, as well as tissuespecific functions is influenced by the cellular organizaÂŹ tion, cell-cell contact and cell-substrate interaction (19)(20)(21)(22).…”
Section: G\l=o"\teborgswedenmentioning
confidence: 99%